COVID-10 and Japan under jishuku: A Japanese Communitarian model to survive disasters - Ito-Morales, Kyoko (Mirai. Estudios Japoneses, 2021)
The year 2020 has been a challenging year to combat against COVID-19. In spite of the globalization and the assimilation of certain political, economic, administrative and cultural practices, the measures taken to protect from COVID-19 are varied according to the countries and their cultures. While Western countries lock down their cities in accordance with the political and juristic orders, the answer Japan gives, namely jishuku, is remarkable and unique. Because it is a voluntary action played by the Japanese citizens and the Communitarian culture developed throughout Japanese history enables to realize such operation. Although still there are a few, studies on the results of jishuku have been progressing. Yet, the origin and the cultural base of jishuku have not been examined sufficiently. Therefore, this study aims to analyze jishuku and surrounding key concepts interdisciplinary. The analysis reveals that the Japanese sociocultural background that closely relates to the frequent tragedies provoked by natural disasters, constructs the culture of jishuku. Moreover, Japan shows an example of a communitarian model to face against some of disasters like the one in which we have been living at present. In addition, it opens us the never-ending discussion on the search for the right balance between the Communitarian model of common good and the Individualist model that defends the individual’s rights.
Keywords: Japan; jishuku; Communitarianism; disasters; COVID-19